Efficacy and Acceptability of Psychotherapy for Anxious Young Children: A Meta-analysis of Randomized Controlled Trials. Issue 12 (December 2017) - Zhang, Hanping; Zhang, Yuqing; Yang, Lining; Yuan, Shuai; Zhou, Xinyu; Pu, Juncai; Liu, Lanxiang; Jiang, Xiaofeng; Xie, Peng
Abstract : Abstract: We aimed to provide an overview of psychotherapy in young anxious children (mean age, <7 years). Seven electronic databases, including PubMed, EMBASE, Cochrane, Web of Science, PsycINFO, CINAHL, and ProQuest Dissertations, were searched. Randomized controlled trials that compared psychotherapies with control conditions were included. Efficacy (score change on an anxiety rating scale and rate of being freed from anxiety) and acceptability (discontinuations due to any event) were evaluated. Six of the total seven studies included in our study adopted cognitive behavioral therapy (CBT), with only one adopting behavior therapy (BT). Psychotherapy effectively reduced anxiety symptoms (standardized mean difference = −0.83; 95% confidence interval [CI], −1.08 to −0.57), and its rate of freeing patients from anxiety was high (risk ratio [RR] = 0.30; 95% CI, 0.19 to 0.47). No remarkable difference for acceptability was found between the two therapy types (RR = 0.54; 95% CI, 0.25 to 1.18). Psychotherapy, both CBT and BT, benefits young anxious children.